Antibiotic-associated changes in Akkermansia muciniphila alter its effects on host metabolic health - Yumin Han; Teh Min Teng; Juwon Han; Heenam Stanley Kim (Microbiome)
Abstract Background Altered gut microbiota has emerged as a major contributing factor to the etiology of chronic conditions in humans. Antibiotic exposure, historically dating back to the mass production of penicillin in the early 1940s, has been proposed as a primary contributor to the cumulative alteration of microbiota over generations. However, the mechanistic link between the antibiotics-altered microbiota and chronic conditions remains unclear. Results In this study, we discovered that variants of the key beneficial gut microbe, Akkermansia muciniphila, were selected upon exposure to penicillin. These variants had mutations in the promoter of a TEM-type β-lactamase gene or pur genes encoding the de novo purine biosynthesis pathway, and they exhibited compromised abilities to mitigate host obesity in a murine model. Notably, variants of A. muciniphila are prevalent in the human microbiome worldwide. Conclusions These findings highlight a previously unknown mechanism through which antibiotics influence host health by affecting the beneficial capacities of the key gut microbes. Furthermore, the global prevalence of A. muciniphila variants raises the possibility that these variants contribute to global epidemics of chronic conditions, warranting further investigations in human populations. Video Abstract